2023
DOI: 10.1177/2515690x231165104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimalarial Activity of Ethanolic Extract ofAnnona muricata L.: Anin vivoand anin silicoApproach

Abstract: In Nigeria, Annona muricata L. has been used to treat a variety of ailments. The mechanism of the antimalarial activity of ethanolic leaf extract of Annona muricata (EEAML) was investigated using both an in vivo and an in silico approach. The experimental mice were divided into five groups: A-F. The mice in groups B-F were inoculated with Plasmodium berghei NK-65 and treated accordingly. Groups A and B are the negative and positive controls (infected and untreated), respectively. Group C received 10 mg/kg chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…Previous in vitro studies have demonstrated substantial antimalarial activity associated with S.hermanni [18][19][20]. The mechanism of action of an active substance as an antimalarial agent often involves the inhibition of key metabolic processes in P. falciparum, preventing the escalation of parasitemia levels [21]. Malaria is an infectious disease that causes severe inflammation and oxidative stress [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies have demonstrated substantial antimalarial activity associated with S.hermanni [18][19][20]. The mechanism of action of an active substance as an antimalarial agent often involves the inhibition of key metabolic processes in P. falciparum, preventing the escalation of parasitemia levels [21]. Malaria is an infectious disease that causes severe inflammation and oxidative stress [22].…”
Section: Introductionmentioning
confidence: 99%